Primary-Secondary Transition – Building Hopes and Diminishing Fears Through Drama - Barlow, William D. (Frontiers in Education, 2021)
This case study explores how pupils might address the issues of bullying and friendships during primary-secondary transition through drama conventions. The research was implemented on the west coast of Scotland during the final four weeks of primary education in three associated primary seven classes. Research methods included pupil questionnaires (primary and secondary school), teacher observations, researcher’s diary, semi-structured interviews (teachers) and a focus group (pupils). The data suggests that some pupils conceptualised their primary-secondary transition as ‘moving up’. However, as the drama developed pupils recognised the multiple and multi-dimensional aspects of their transition. In addition, pupil and teachers indicated that when pupils engage with a drama transition curriculum, it supports the promotion of friendships while diminishes fears and provides strategies for those who might encounter bullying.